Soft Matter Emerging Investigators 2019. Issue 6 (30th January 2019) - Pochan, Darrin
Abstract : This themed issue of Soft Matter highlights the work of emerging investigators in the field of soft matter. Editor-in-Chief Darrin Pochan introduces the issue.